TV Islam International (Southern California : Islamic Information Service, 1900)
The video potrays different aspects of Islam in practice
Vol.1. Resurgent Islam: California, London ; Islamic Call Society: Canada, L ibya - Vol.2. Resurgent Islam: prison (1,2) ; Women in Islam ; Are our children living double lives? - Vol.3. Resurgent Islam: Media, political awarenwss,human rights ;'Satanic mind' - Vol.4. Worship in Islam ; Ramadhan in Canada ; Eid-El-Fitr ; Hajj - Vol.5. The freedom of no choice: the truth (1,2) ; Science Centre, Dr.Whitehouse - Vol.6. Islam in Rome ; A man and his art ; Islamin Spain - Vol.7. Islamic horizon (1,2) ; Islam in Yugoslavia (1,2) - Vol.8. Transformation ; The plight of Muslims in Sri Lanka (1,2,3) - Vol.9. Islam inMalaysia (1,2,3,4) - Vol.10. Islam, Egypt and the Gulf Crises (1,2,3) ; Man and nature - Vol.11. Resurgent Islam: Barbados (1,2,3) ; Trinidad - Vol. 12. Inner awakenning (1,2,3,4) with Shaykh Fadhialla Haeri
Copy available in DVD format
Copy available in DVD format
Keywords: Islam -- 20th century